The Neuropeptide Galanin Benefits Insulin Sensitivity in Subjects with Type 2 Diabetes - Fang, Penghua; Yu, Mei; Shi, Mingyi; He, Biao; Zhang, Zhenwen; Bo, Ping (Current Protein and Peptide Science, 2013)
Impaired insulin sensitivity, namely insulin resistance, is a metabolic and functional disorder that is often associated with the type 2 diabetes mellitus and/or obesity. Recent studies have provided compelling clues that the neuropeptide galanin is closely related to insulin sensitivity in skeletal muscle and adipose tissue of rats. This peptide may regulate glucose homeostasis and carbohydrate metabolism in peripheral tissues, as well as accelerate the translocation of glucose transporter 4 to the plasma membrane of various insulin-sensitive cells to reduce insulin resistance. Galanin plays a crucial role in inhibiting insulin secretion from pancreatic β cells to prevent hyperinsulinemia, which is a characteristic of type 2 diabetes mellitus. This review provides a comprehensive aggregation of the current literature available, bringing together data gleaned from our recent studies highlighting the role of galanin in regulating insulin sensitivity. This comprehensive role played by galanin and its relative agents in regulating insulin secretion and insulin sensitivity provides a new insight into the influence of this neuropeptides on the prevention and treatment of type 2 diabetes mellitus.
Keywords: Galanin